The Development Status of Edge Computing - Zhongkai Zhang, Tong Zhen, Zhihui Li, Jianjun Wu (Forest Chemicals Review)
It is the rapid development of the Internet and the Internet of Things technology that makes the cloud computing model of storing data in the cloud and using the powerful server of the cloud have many shortcomings and cannot solve the existing problems well. Therefore, the concept of edge computing is further extended on the basis of cloud computing. Edge computing is a special computing model. Its main body mainly acts on the edge of the network. By using edge nodes with computing and resource attributes between the source of the data terminal and the cloud center, the data source data is analyzed and processed under ideal conditions. , Save and reduce network traffic and response time. With the continuous progress and development of edge computing, the architecture of edge computing has gradually improved, but at the same time each has its own advantages and disadvantages. This article mainly compares the more popular edge computing reference framework 3.0 and EdgeX Foundry architecture.